DEVELOPING OF E-LEARNING BASED MATHEMATICS LEARNING MODULES TO IMPROVE PROBLEM SOLVING SKILLS OF STUDENTS - Vera Riyanti; Yuli Budhiarti; Iis Istika (USN Kolaka, 2024)
The availability of learning modules that are valid and easy for students to understand is essential for achieving educational objectives. Limited problem solving skills in the fundamental concepts of ordinary differential equations pose a significant challenge in the learning process. This research aims to enhance students' problem-solving abilities in the topic of ordinary differential equations through the development of a mathematics e-learning modules for students in the Mathematics Education Study Program. The research method employed is the ADDIE development model. Based on the research findings, the developed e-learning modules was validated by subject matter experts, yielding a score of 3.61, categorized as very good, while validation by media experts resulted in a score of 3.42, also categorized as very good. The evaluation from students regarding the e-learning modules received a score of 3.81, which falls into the very good category. Based on the assessment of quiz responses, the average score was 78.9, indicating an improvement in students' problem-solving abilities prior to using the e-learning modules, which had an average score of 59.8. It can be concluded that the e-learning modules on the concepts of ordinary differential equations is suitable for use in learning and can enhance students' problem-solving skills.